An experimental study of the physical mechanisms of fluid flow in tight carbonate core samples by binary surfactants - Ayomikun Bello; Anastasia Ivanova; Alexander Rodionov; Tagir Karamov; Andrey Morkovkin; Alexey Cheremisin (Heliyon)
Binary surfactants present a promising approach to modifying the petrophysical mechanisms of rock formations to enhance fluid flow, particularly in challenging environments like carbonate rocks. Carbonate rocks exhibit a complex surface charge, which makes it difficult to generalize the use of traditional single surfactants. Hence, the application of binary surfactant systems is proposed as a more effective alternative. This study investigates fluid-rock interactions through adsorption, wettability alteration, and spontaneous imbibition tests. First, static adsorption tests were conducted on eight different surfactant systems to compare the adsorption behaviors of the binary surfactant systems with those of individual surfactants. The results showed a significant influence of the nonionic surfactant with a considerable reduction in adsorption values of 53% and 28% in its anionic-nonionic and cationic-nonionic blends, respectively. Although contact angle measurements taken after aging oil-treated carbonate discs in binary surfactant solutions indicated that wettability was not significantly altered, the binary systems demonstrated the highest efficiency in terms of oil production during spontaneous imbibition tests. Specifically, the zwitterionic-nonionic surfactant system recovered 58% of the initial oil in core samples, compared to 31% and 25% when zwitterionic and nonionic surfactants were used individually. Thus, the use of binary surfactant systems shows great potential for improving oil recovery efficiency, and the findings may have broader implications for optimizing filtration mechanisms in carbonate reservoirs.